Brief Primer on Tools to Prioritize a Research and Innovation Portfolio in a Complex System Involving Multiple Decision Makers - CGIAR Independent Science for Development Council (CGIAR Independent Advisory and Evaluation Service, 2025)
This Brief Primer on Tools to Prioritize a Research and Innovation Portfolio in a Complex System Involving Multiple Decision Makers equips System Council and CGIAR leadership with ISDC tools (2020-2025) to guide difficult funding and research allocation choices amid shrinking resources and expanding global challenges. It outlines methods to make prioritization transparent, consistent, and defensible, integrating both top-down and bottom-up perspectives.